Status and effects of health workforce related factors on implementation of universal health care in Nakuru West Sub County, Nakuru, Kenya - Selvesta, Jackline Mokeira; Esilaba, Moses Otiati; Donde, Oscar Omondi (International Journal Of Community Medicine And Public Health, 2020)
Background: Globally, due to low health care coverage, there have been continued efforts to ensure that there is increased accessibility to quality, affordable and equitable universal health care (UHC) services in most parts of developing countries, such as within Nakuru county in Kenya. Methods: The study focused on determining health workforce gaps in health care facilities that might affect the implementation of UHC in Nakuru West Sub County. Cross-sectional study design was applied, data was collected using structured questionnaires, analyzed using statistical package for social sciences 23rd version and presented in charts for ease comparison. Results: The findings of this study indicated that there was shortage of HWCs. This implies that the staffing in the facilities located in Nakuru West Sub-County is inadequate for the implementation of the Kenyan government UHC and it was evident that the mostly affected sections were the nursing, public health officer (PHO), pharmacy, clinical officers and laboratory in that order. Most alarmingly, majority of the HCWs (58.2%) were not being appreciated for good work, despite the fact that they play a key role in the implementation of UHC. Conclusions: It is therefore imperative for the county government which is the arm of the Kenyan government to ensure that they recruit adequate health care workers in all cadres to serve the continuously rising population and HCWs should have adequate level of education, acceptable training skills and be well- motivated.